Synthesis and Application of Dendritic Fibrous Nanosilica/Gold Hybrid Nanomaterials. Issue 5 (16th May 2018) - Byoun, Wongyun; Jung, Soeun; Tran, Ngoc Minh; Yoo, Hyojong
Abstract: Morphologically unique silica nanoparticles can be used as effective templates to prepare silica–metal hybrid nanomaterials, which are highly applicable in a variety of areas. Mesoporous silica nanoparticles, which have high surface areas and an abundance of pores, can be used to synthesize mesoporous silica core–metal shell nanostructures with catalytically active sites. In this work, dendritic fibrous nanosilica (DFNS) with a high surface area is successfully employed as a template to synthesize DFNS/Au hybrid nanomaterials. Au nanodots are initially synthesized through the selective reduction of Au ions on the surface of the DFNS after surface modification to form DFNS/Au dots. A seed‐mediated growth method is used to controllably grow Au nanoparticles on the DFNS/Au dots to generate DFNS core–Au nanoparticles shell nanohybrids (DFNS/Au NPs) and DFNS core–Au layer shell nanohybrids (DFNS/Au layers). The catalytic activities of DFNS/Au NPs and DFNS/Au layers in the 4‐nitrophenol reduction reaction are compared. Abstract : Plant the seed : Dendritic fibrous nanosilica (DFNS) with a high surface area is successfully employed as a template to synthesize DFNS/Au hybrid nanomaterials. A seed‐mediated growth method is used to controllably grow Au nanoparticles to generate DFNS/Au NPs and DFNS/Au layers. The catalytic activities in the 4‐nitrophenol reduction reaction are compared.